Spontaneous intracerebellar haemorrhage and hydrocephalus: a case report - Yovi Eko Azhra; M Ihsan Z Tala; M Deni Nst (DiscoverSys Inc., 2020)
Background: Hemorrhagic strokes affect more than 1 million people every year worldwide and are the most frequent type of stroke with high mortality and morbidity rates. Spontaneous Intracerebral Hemorrhage (SICH) often affects the basal ganglia, thalamus, cerebral lobes, pons, and cerebellum.Case Description: In this report, we present a 63-year-old female with sudden onset loss of consciousness and computed tomography (CT) of head demonstrated an intracranial haemorrhage in the cerebellum with hydrocephalus. The existence of hydrocephalus and the development of chronic hydrocephalus is a problem, awaiting a solution in patients who didn’t undergo surgical treatment for cerebellar haemorrhage; however, it can easily be treated effectively by surgical evacuation.Conclusion: A general practitioner should be able to carry out appropriate initial management to reduce morbidity and mortality.